Pelatihan Hasil Belajar Matematika Melalui Model Problem Basic Learning Dengan Melalui Curipot Sekolah UPT SDN 064986 Medan Amplas T.P 2024 - Saiful Bahri; Samsul Bahri; Bambang Hermanto; Muhammad Hilman Fikri (LPPI UMN AL WASHLIYAH, 2025)
Based on the Objectives of Mathematical Concepts: so that students can understand and solve mathematical problems. Understanding mathematical concepts can also help students understand advanced lessons and solve problems in the world of work. Mathematical Concepts are the understanding, characteristics, specifics, nature, and content of mathematical material. Some of the objectives of learning mathematics, then the problems faced by students are: (1) improving intellectual abilities (2) training communication (3) developing student character (4) reasoning (5) connecting (6) proving (7) designing (8) improving knowledge attitudes and behavior. Assistance activities and training of mathematical learning outcomes through the basic learning problem model through the school curipot UPT SDN 064986, Medan Amplas District. In order for the purpose of learning mathematics to improve student learning outcomes with the concepts that have been applied by the teacher in the learning process and innovative students aim to help solve problems that are worked on individually and students of SDN 064986 Medan Amplas District are active in the learning process in the classroom. What we have implemented the purpose of the mathematical concept is achieved: so that students can understand and solve mathematical problems and understanding mathematical concepts can also help students in understanding advanced lessons and solving problems in the world of work.